PENINGKATAN KREATIVITAS BERPIKIR DAN PRESTASI BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE DALAM MATA PELAJARAN MEKANIKA TEKNIK II SMK NEGERI 2 SURAKARTA - Rohmawati, Ulfia Atmaha (Jurnal Nosel, 2015)
The objective of this research is to improve the thinking creativity and the learning result of the students in Grade X of State Vocational High School 2 of Surakarta in the subject matter of Technical Mechanics II through the use of the Cooperative Learning Model of the Think Pair Share type.This research used the classroom action research with three cycles. Each cycle included planning, implementation, observation, and reflection. The subjects of research were the students as many as 32 in Grade X of TPM B of State Vocational High School 2 of Surakarta. The data sources of research were a teacher and students. The data of research were collected through in-depth interview, observation, documentation, and test.Validated by using the construct one. The item analysis used the computer program of Iteman 3.00. The data were analyzed by using the descriptive comparative model of analysis in the forms of percentage and mean ideal.The results of this research show that the application of the Cooperative Learning Model of the Think Pair Share type can improve the students? thinking creativity. Prior to the treatment, the percentage of the students? thinking creativity is 30.41%. Following the treatment, it becomes 54.63% in Cycle I and 80.52% in Cycle II respectively. The indicators of thinking creativity include fluency, flexibility, elaboration, sensitivity, originality, novelty, and use of new approach use. The application of the cooperative learning model of the think pair share can improve the students? learning result. Prior to the treatment, the percentage of the students? learning result is 71.87%. Following the treatment, it becomes 81.25% in Cycle I and 87.50% in Cycle II respectively. Prior to the treatment, the learning result score average is 74.60. Following the treatment, it becomes 76.75 in Cycle I and 81.05 in Cycle II respectively. Thus, the application of the Cooperative Learning Model of the Think Pair Share type can improve the thinking creativity and the learning result in learning the subject matter of Technical Mechanics II of the students in Grade X of State Vocational High School 2 of Surakarta in Academic Year 2014/2015.